THE IMPACT OF MATERNAL STRESS IN PREGNANCY ON THE INFANT UNTIL THE CHILD - Nurul Fadilah, R.A. Rahmawati; Nafiati, Dini Latifatun (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2025)
Introduction - The gestation period is a time of significant psychological and neurobiological changes. This is often associated with stress in the mother and the increased risk of psychopathology. This will also have an impact on the baby conceived by the mother and will even affect the newborn to have an impact on the way the mother parenting for her child which will also have an impact on the growth and development of the child. The purpose of this study was to see the impact of stress on pregnant women on fetal development up to childhood. This research was made based on a literature review. Methods - The literature used in this study is a review of research articles only. This study concludes that exposure to stress during pregnancy can have an impact on the fetus, baby, and even childhood. Results - The impact on the fetus is influential on heart rate variability (HRV), and the incidence of small gestational age (SGA). The impact on infants is the incidence of infectious diseases and allergies in infants, affecting the development of the baby's brain, temperament, and stress in infants, to the cognitive development of infants. Discuss - The influence on children is the amount of cortisol and the incidence of anxiety in children, the incidence of mental illness and behavior, to affect parenting in children. Conclusion - The impact on children is influential on the amount of cortisol and anxiety events in children, affects the incidence of mental illness and behavior, and affects parenting in children. The above can have a long or short effect on the child's next life. Therefore, it is hoped that this study can provide more awareness and attention to pregnant women, especially their mental health.